A Novel Arthropod Host of Brucellosis in the Arid Steppe Ecosystem - Huang, Tianpeng; Zhang, Jinbao; Sun, Changyun; Liu, Zhicheng; He, Haiyan; Wu, Jie; Geriletu, (Frontiers in Veterinary Science, 2020)
Brucellosis is a severe public health problem in the Inner Mongolia regions of China. The recent prevalence of Brucellosis outbreaks in recent times may be attributed to the increased activity of ticks and other air-borne vectors. Dermacentor nuttalli (D. nuttalli) is a native tick species from inner Mongolia, and similar to other tick species, D. nuttalli carry a variety of pathogens that can be transmitted to a wide range of animals. In this work, we have investigated the potential of D. nuttalli to cause Brucellosis. Between 2015 to 2019, 2256 ticks were collected from 23 different pastoral areas of Hulun Buir. For Brucellosis pathogen detection, DNA was extracted from ticks at different stages of development. Salivary gland and midgut tissue samples were used as templates for the amplification of Brucella Bscp31 gene (Brucella species-specific gene), by TaqMan Real-Time PCR. Bscp31 protein of Brucella was detected by Western blot and Immunofluorescence in the midgut and salivary gland tissues of D. nuttalli. Additionally, Brucella isolation in the culture medium of Brucella was performed. Tick samples were identified as D. nuttalli. Different percentage of Brucella specific genes could be found in the tick samples as confirmed by PCR. Between 2015 to 2019, the positive rate for the detection of Bscp31 gene in D. nuttalli ranged from 0.00% to 87.80%, with the highest rate being 89.00%. In addition, Brucella specific genes were successfully detected in the samples isolated from all developmental stages and different parts of ticks. Western blotting and immunofluorescence also showed that the Bscp31 protein was present in the midgut and salivary gland of D. nuttalli. Further, B. melitensis biotype 3 was isolated from eggs and engorged of D. nuttalli, Respectively. These findings demonstrate that D. nuttalli is a potent, long-term carrier of Brucella and can exhibit transovarial transmission, posing D. nuttalli as a novel arthropod host for Brucella. This therefore puts forth the potential risk of the spread of Brucellosis via tick bites among animals as well as human beings.